Smartphone Apps for Mindfulness Interventions for Suicidality in Asian Youths: Literature Review - Choo, Carol C; Burton, André AD (JMIR Publications, 2018)
BackgroundThe advent of mobile technology has ushered in an era in which smartphone apps can be used as interventions for suicidality. ObjectiveWe aimed to review recent research that is relevant to smartphone apps that can be used for mindfulness interventions for suicidality in Asian youths. MethodsThe inclusion criteria for this review were: papers published in peer-reviewed journals from 2007 to 2017 with usage of search terms (namely "smartphone application" and "mindfulness") and screened by an experienced Asian clinician to be of clinical utility for mindfulness interventions for suicidality with Asian youths. ResultsThe initial search of databases yielded 375 results. Fourteen full text papers that fit the inclusion criteria were assessed for eligibility and 10 papers were included in the current review. ConclusionsThis review highlighted the paucity of evidence-based and empirically validated research into effective smartphone apps that can be used for mindfulness interventions for suicidality with Asian youths.